(untitled) (Research, Society and Development, 2021)
Solution of nonlinear optimization problems with equality and inequality constraints is a hard task and tend to be more complex when involves a large number of variables. Energy and control systems and chemical plants are represented by this type of problem. With technological and computational progress, its necessary use effective tools that can handle with characteristics of this type of systems, effectively solving optimization problem. In this work, we solve two classical problems of nonlinear optimization with constraints of chemical process in free software Scilab, using the function fmincon, in order to evaluate the performance of the algorithm for solving constrained nonlinear programming problems. Results are compared with optimal conditions obtained with Matlab. Free software shows a good performance, achieved effective results and finding points thata results in a increase of 16% in objective function to investiment return of Williams-Otto plant, showing itself an efficient alternative for the development of research and technology in this field.